MANAJEMEN INOVASI PENDIDIKAN ERA PANDEMI COVID-19 (Studi Kasus di SMKN 7 Technopreneur Merdeka Kabupaten Kaur) - Fetri, Gunita Herya; Danim, Sudarwan (Manajer Pendididikan, 2023)
Purpose of study was to describe management of educational innovation in the Covid-19 pandemic era atSMKN 7 TMKK. Research is descriptive qualitative. Research subjects were vice principals, teachers and parents ofstudents at SMKN 7 TMKK. Collecting data using observation, interviews and documentation. Data analysis wascarried out with steps of data reduction, data presentation, verification and drawing conclusions. Results show thatthe management of educational innovation in the Covid-19 pandemic era which consists of aspects of planning, taskdivision systems, budgeting systems, supervision, quality assurance and the obstacles faced have been proven throughthe process and it is necessary to improve the quality of several components. Innovations that look good and haveproducts in process are in development of learning tools, that is implementation of learning plans during Covid-19pandemic made by teachers and production of ginger powder marketed by SMKN 7 TMKK students in supportingefforts to increase community immunity with herbal drinks that healthy